Rationing of nursing care in Internal Medicine Departments-a cross-sectional study - Maria Jędrzejczyk; Beata Guzak; Michał Czapla; Catherine Ross; Ercole Vellone; Jan Juzwiszyn; Anna Chudiak; Mikołaj Sadowski; Izabella Uchmanowicz (BMC, 2023)
Abstract Background Implicit rationing of nursing care refers to a situation in which necessary nursing care is not performed to meet all of the patients' needs. Purpose To examine the factors influencing the rationing of nursing care, nurses' assessment of the quality of patient care, and their job satisfaction in Internal Medicine Departments. Methods A cross-sectional descriptive study was undertaken. The study included 1164 nurses working in the Internal Medicine Departments in 8 hospitals (Lower Silesia, Poland). The Perceived Implicit Rationing of Nursing Care instrument was used. Results Respondents rarely ration nursing care, with a mean score of 1.12 (SD = 0.68). The mean score for quality of patient care was 6.99 (SD = 1.92). In contrast, the mean job satisfaction score was 6.07 points (SD = 2.22). The most important predictors of high rates of rationing of nursing care were work experience of 16-20 years (regression parameter: 0.387) and a Bachelor's degree in nursing (regression parameter: 0.139). Nurses' assessment of the quality of patient care ratings were increased by having a Master's degree in nursing (regression parameter: 0.41), and significantly decreased by work experience of 16-20 years (regression parameter: -1.332). Independent predictors of job satisfaction ratings in both univariate and multivariate analysis were Master's degree and long-shift working patterns. Conclusion The factors that influence an increased level of nursing care rationing on medical wards are nurse seniority, exceeding 16 years and female gender. Obtaining a Master's degree in nursing indicates improved nurses' assessment of the quality of patient care.